The influence of Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operational Expenses on Operating Income (BOPO) on profitability of Bank Syariah Indonesia - Mutiara Yolanda; Muhammad Lathief Ilhamy Nasution (Enrichment : Journal of Management, 2023)
This study aims to determine the effect of financial ratios on the profitability of Bank Syariah Indonesia. The financial ratios used in this study are Non-Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operating Expenses to Operating Income (BOPO), as well as Return on Assets (ROA). With Time series data for the period 2018/1-2022/4. The method the researchers used was the quantitative method, using the NPF, FDR, and BOPO variables through the Classical Assumptions Test, Multiple Linear Regression, t-test, F-test, and R2-test. The data taken is secondary data from the financial statements of Bank Syariah Indonesia which are published by www.bankbsi.co.id to test the validity of the data. The results of the study showed that NPF and BOPO had a significant negative effect on ROA and FDR had a significant positive effect on ROA. Therefore, to increase the profit of Bank Syariah Indonesia, it is necessary to increase financing (increase FDR) with low risk (low NPF) and bank efficiency (lower BOPO).